2024
DOI: 10.1038/s41598-024-59344-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cardiac oxidative stress, inflammatory cytokine response, cardiac pump function, and prognosis post-myocardial infarction

Dongpeng Duan,
Hongjun Li,
Shiyun Chai
et al.

Abstract: This study delves into the potential connections between cardiac oxidative stress, inflammatory cytokine response, cardiac pump function, and prognosis in individuals following myocardial infarction. A total of 276 patients were categorized into two groups: the control group (n = 130) and the observation group (n = 146), based on the drug intervention strategies. The control group received standard drug treatment, while the observation group received early drug intervention targeting antioxidant and anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Inflammatory reactions exist in both acute and chronic cardiovascular diseases, vascular endothelial cells are the main site of systemic inflammation or local inflammatory response [ 173 ]. Numerous studies have shown that inflammation is one of the main driving mechanisms of cardiovascular disease [ 174 , 175 ]. However, the inflammatory response of endothelial cells plays a crucial role in the pathogenesis of cardiovascular diseases.…”
Section: The Mechanism Of Tongxinluo In Preventing and Treating Cardi...mentioning
confidence: 99%
“…Inflammatory reactions exist in both acute and chronic cardiovascular diseases, vascular endothelial cells are the main site of systemic inflammation or local inflammatory response [ 173 ]. Numerous studies have shown that inflammation is one of the main driving mechanisms of cardiovascular disease [ 174 , 175 ]. However, the inflammatory response of endothelial cells plays a crucial role in the pathogenesis of cardiovascular diseases.…”
Section: The Mechanism Of Tongxinluo In Preventing and Treating Cardi...mentioning
confidence: 99%